Kamba carvers - Tracey, Andrew (International Library of African Music, 1960)
The Kamba are closely related to the Kikuyu of Kenya, but unlike these they have a reputation for soldiering as with the Tonga of Nyasaland. 30 K.A.R., among other battalions, has a large number of Kamba, and so has the Kenya police force. This, strangely, may have something to do with the fact that so many men of the tribe have now taken enthusiastically to carving. Their tradition in wood carving was very slight, similar to that of many of their neighbours, being limited to such articles as spoons, stools and medicine horn stoppers, but the present craft seems to have started during the first world war when a number of Kamba soldiers found themselves stationed in Dar-es-Salaam. Amongst them was a man called Mutesya waMunge. The WaZaramu of Dar-es-Salaam had already been carving for a long time, having originally received the craft, so the Kamba say, from the Ceylonese, and they were best known for their expertly worked heads in ebony. Mutesya learnt their craft, and on his return to Wamunyu, his home district of Kambaland, he began to carve professionally.
Keywords: Wood-carving; Wood-carvers; Kamba (African people); Handicraft; Ethnomusicology; Ethnology; Kenya; African Music